The impossibility of a moral right to privacy - Persson, I; Savulescu, J (Springer, 2022)

(untitled)
This paper clarifies and defends against criticism our argument in Unfit for the Future that there is no moral right to privacy. A right to privacy is conceived as a right that others do not acquire information about us that we reserve for ourselves and selected others. Information acquisition itself is distinguished from the means used to acquire it and the uses to which the information is put. To acquire information is not an action; it is to be caused to be in an internal state. By contrast, means of acquisition and uses of information are actions that can be voluntarily controlled. We can therefore have rights against others that they stay away from certain means and uses but not from information acquisition in itself. An omniscient, omnipotent and omnibeneficient being is not thought to violate a right to privacy because its means and uses of information are morally acceptable.